Health Campaign on the Dangers of Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) in Tanjung Village - Retno Dwi Jayanti; Anisa Nuraini; Fina Septiya; iik Sartika (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Based on data from the Sukoharjo Regency AIDS Control Commission (KPA), HIV/AIDS cases show an increasing trend, with 102 new cases in 2023 compared to 82 cases in 2022. Data for January 2024 also shows 6 new cases. The accumulation from 2008 to January 2024 reached 930 cases spread across all sub-districts, including 62 cases in Nguter District. The purpose of this activity is to increase the awareness of the people of Tanjung Village about HIV/AIDS, reduce stigma against ODHA, and encourage an inclusive and empathetic attitude towards ODHA. Target achievement is measured through the level of active community participation in activities and the distribution of campaign materials. The method used is a participatory method, which involves the community directly in various. activities, such as healthy walks, joint gymnastics, herbal medicine drinking movements, distribution of educational posters and stickers, and free health checks. This activity was held on August 25, 2024 at Latar Ombo, Pencol, Tanjung Village, with participants coming from various circles, ranging from children to adults, and attended by village officials and sub-district officials. The results of the activity showed a success of 80% based on program indicators, marked by high community participation in the entire series of events, the exhaustion of all posters, stickers, and herbal medicine distributed, and the crowded health checkpoints. The community shows high enthusiasm and a better understanding of HIV/AIDS. In conclusion, this campaign is effective in raising awareness and reducing stigma against ODHA in Tanjung Village. For future implementation, continuous education efforts and cross-sectoral collaboration are needed to ensure that this change in attitudes can be sustained and extended to a wider region. Keywords: HIV/AIDS, Campaign, stigma and discrimination.